Persepsi Siswa Terhadap Pelaksanaan Pembelajaran Seni Rupa di SMA Negeri 3 Kota Solok - DINI PEBRIANI, Drs. Eswendi, M.Pd, Drs. Erwin A, M.Sn (Serupa The Journal of Art Education, 2014)
This research aim to know children perception to do fine art learning about 1)to open and close teaching skill, 2) question skill, 3) to give reinforcement skill, 4) stimulus and variation skill, 5) to manage classroom. Population in research is all children SMA Negeri 3 Kota Solok amount to 1102 and sampel amount to 268 of children. This research is descriptive research as a problem solving procedure. Sample technic use stratified propotional random sampling. Result of research show is children perception to fine art teacher is good enough.Key word: children perception, learning and instruction